Implementation of nutrition screening for older adults in general practice: Patient perspectives indicate acceptability - Hamirudin, Aliza Haslinda; Charlton, Karen; Walton, Karen; Bonney, Andrew; Albert, George; Hodgkins, Adam; Ghosh, Abhijeet; Potter, Jan; Milosavljevic, Marianna; Dalley, Andrew (Journal of Aging Research & Clinical Practice, 2016)
Background: Older patients’ views regarding undergoing nutrition screening within General Practice settings have not been evaluated to date. Objectives: To identify perceptions of older patients related to their experiences of having a nutrition screening process performed using the Mini Nutritional Assessment Short Form (MNA-SF®), accompanied by a clinical care pathway. Methods: Patients aged ≥75 years were invited to attend repeat screening between 6 months and one year following a first screening (n=143). Patients who were identified to be malnourished or at risk at baseline (n=44) were invited to participate in an individual interview to identify their perceptions of the MNA-SF® and the applicability of a nutrition resource kit that had been provided to them. Results: Nutritional status improved in the group identified to be malnourished/at risk at baseline (p= 0.01). Interviews indicated that the MNA-SF® process was well-received but that patients did not perceive themselves as being in need of nutrition support. Conclusion: This study demonstrates that introduction of routine nutrition screening of older patients attending General Practice can feasibly be implemented using the MNA-SF® and is acceptable to patients. It is recommended that this model of care be adopted in order to improve early identification of nutritional risk and facilitate referral to appropriate services.